DIVERSITY MANAGEMENT AND EMPLOYEE PERFORMANCE OF BREWING FIRMS IN ANAMBRA STATE, NIGERIA. (Journal of the Management Sciences, 2024)
The increasing differences in the workplace environment negatively affect the team spirit expected among employees to enhance their productivity and sustainability within the ambit of the organization. This work examined the relationship that exists between diversity management and employee performance of brewing firms in Anambra State, Nigeria. Specifically, objectives were categorically drawn to ascertain the extent of relationship that exists between gender diversity and job position of worker; to determine the relationship that exists between age diversity and employee commitment; and to examine the nature of the relationship that exists between cultural diversity and employee satisfaction in brewing firms in Anambra State. Descriptive survey design was adopted. The population of the study stood at 1284 and a sample size of 305 was arrived at using Taro Yamane Formula. Data were collected via structured questionnaire, and was analyzed using descriptive statistics of frequency table and percentages. Hypotheses were tested using Pearson Product Moment Correlation Coefficient with the aid of Statistical Package for Social Sciences (SPSS version 27). Results revealed significant positive relationship between gender diversity and job position; significant positive relationship between age diversity and employee commitment; significant positive relationship between cultural diversity and employee satisfaction. We concluded that all the three proxies (gender diversity and job position of workers, age diversity and employee commitment, cultural diversity and employee satisfaction) showed significant positive relationships. Based on the findings, we recommended that organizations need to be gender sensitive during recruitment to ensure that job positions of workers are skewed appropriately. Also, organizations need to design suitable diversity management programme that will ensure an effective and efficient job descriptions, and that cultural differences are tolerated among the employees to ensure employee satisfaction in brewing firms in Anambra State, Nigeria..
Keywords: Diversity management, employee performance, gender diversity, cultural diversity, brewing firms.